Leadership of the Principal in Planning the Internal Quality Assurance System at Islamic Elementary School - Zaenab Hanim; Kaolan Kaolan; Adam Juit; Jati Kesuma; Rahmat Soeoed (EduLine: Journal of Education and Learning Innovation, 2022)
The purpose of this research is to describe the principal’s leadership in planning the internal quality assurance system (IQAS) of Al Azhar School in terms of content, process, and assessment standards. This research used a qualitative approach with a case method. The subjects of the research were principal, teachers, students, and parents of students. Data were collected by using in-depth interviews, observation, and documentation. The validity of the research data was done through triangulation. The data analysis model used was an interactive data analysis developed by Miles and Huberman through several stages, starting from data collection, data reduction, data presentation, and data verification or conclusion. The research findings showed that the principal's leadership in planning the internal quality assurance system was indicated by his School Income and Expenditure Budget Plan (SIEBP) carried out through school meetings by involving different school development teams such as curricular, exclassical, religious, and support teams as well as school committee. He carried out quality improvement through comparative studies and collaboration with other institutions stated in the memorandum of understanding. He also made a special team to carry out internal quality improvements related to content standards, educational processes, performance assessments, giving certificate of award and salary increase for teachers who achieve work performance. In addition, he also ran academic and non-academic activities as a continuous internal quality improvement for achieving National Education Standards (NES).